The Values of Multicultural Education According to Modern Tafsir: A Thematic Study of Tafsir al-Maraghi and Tafsir al-Mishbah - Salamudin, Ceceng; Abdullah, Deba Muslim; Maria, Anly (LP. Ma'arif Janggan Magetan, 2024)
Many horizontal conflicts and acts of violence arise from erroneous human perspectives on social, cultural, and religious diversity. In Islam, the Qur’an functions as a fundamental source of values and paradigms guiding Muslim attitudes toward such differences. This study examines the values of multicultural education derived from modern Qur’anic interpretations of QS. Al-Baqarah [2]: 62, 213, 256, an-Nisa [4]: 36, 135; al-Maidah [5]: 2, Ali-Imran [3]: 15, 134, al-Ḥujurāt [49]:11-13, a verse that explicitly addresses human diversity, equality, and moral merit based on piety (taqwā). The research focuses on Tafsir al-Maraghi and Tafsir al-Mishbah, selected as representative works of modern tafsir due to their rational, contextual, and socio-ethical approaches to Qur’anic interpretation. Using a descriptive qualitative method with a thematic (mawḍū‘ī) interpretation approach, the study analyzes how these tafsir conceptualize diversity and social relations. The findings indicate that articulate four core values of multicultural education: (1) learning to live with differences, (2) mutual respect among individuals and groups, (3) interdependence among human beings, and (4) non-violent conflict resolution and reconciliation. Rather than offering direct or complete solutions to conflict and violence, these values provide a conceptual and ethical framework that can contribute to the development of multicultural awareness and peaceful coexistence in plural societies.